Time spent on the Internet, problematic gaming and social media use among adolescents - Sophia Berber; Katrin Potzel; Rudolf Kammerl; Lutz Wartberg; Caroline Meyer (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung, 2025)
Increased Internet use during the COVID-19 pandemic and the possibility of problematic usage patterns and associated disorders among adolescents has become an important research topic. The longitudinal quantitative study presented in this article examines changes in adolescents’ use of online games and social media over the four-year period 2018 to 2021, focusing on the existence of problematic patterns before and during the COVID-19 pandemic. Data were collected from adolescents and one parent each (multi-perspective approach) at intervals of one year (four measurement points, t3 to t6). The sample consisted of 852 dyads at t3, with 474 dyads remaining in the sample at t6. The adolescents were between 13 and 16 years old at t3; Young people with problematic Internet usage were oversampled. Statistical analyses of the data comparing mean values show that the total time spent online, the time spent on gaming, and the time spent using social media increased significantly over the period under investigation. However, the results clearly show that problematic gaming and problematic usage of social media decreased significantly: Increased time spent on gaming and social media was not associated with problematic usage patterns. Rather, problematic use decreased significantly over the period, which included the COVID-19 pandemic (2020–2021). These findings run counter to results of past studies that reported a rise in problematic usage patterns during the COVID-19 pandemic. Although our results show an increase in digital media usage during this four-year period, that increase was not accompanied by more problematic usage patterns.